2012
DOI: 10.1016/j.psyneuen.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the diurnal cortisol profile in children and adolescents

Abstract: SummaryThe diurnal cortisol profile has been implicated in multiple physical and mental health conditions in children and adolescents; however, current knowledge regarding the stability of the diurnal cortisol profile is largely based on adults. Developmental changes throughout childhood and adolescence warrant examination of the stability of the diurnal cortisol profile during this stage in the lifecourse. The aim of the present study was to conduct a comprehensive evaluation of the diurnal cortisol profile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 49 publications
11
93
0
Order By: Relevance
“…To accurately capture the cortisol awakening response (CAR) individuals must be compliant with saliva sampling, which includes collecting a sample immediately upon waking (awake 0 sample). Compliance with this initial sample is also important for other measures of the diurnal cortisol profile (e.g., diurnal slope), as they too use the awake 0 sample in their calculation (Adam and Kumari, 2009;Rotenberg et al, 2012). To date, most research has exclusively focused on verifying self-reported sampling time with an objective measure of time, such as an electronic monitor that date-and time-stamps bottle opening and presumed time of saliva collection (e.g., MEMS Cap; Kudielka et al, 2003;Broderick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To accurately capture the cortisol awakening response (CAR) individuals must be compliant with saliva sampling, which includes collecting a sample immediately upon waking (awake 0 sample). Compliance with this initial sample is also important for other measures of the diurnal cortisol profile (e.g., diurnal slope), as they too use the awake 0 sample in their calculation (Adam and Kumari, 2009;Rotenberg et al, 2012). To date, most research has exclusively focused on verifying self-reported sampling time with an objective measure of time, such as an electronic monitor that date-and time-stamps bottle opening and presumed time of saliva collection (e.g., MEMS Cap; Kudielka et al, 2003;Broderick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Adult findings cannot be generalized to children and adolescents due to several developmental factors that influence the diurnal cortisol profile (Rotenberg et al, 2012). Developmental factors during childhood and adolescence influence awake 0 sampling (e.g., school routine, changes to sleep/wake pattern; Jessop and Turner-Cobb, 2008) as well as the cortisol response.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations